Single-fraction HDR brachytherapy as monotherapy in low and intermediate risk prostate cancer: Outcomes from two clinical trials with and without an MRI-guided boost. (January 2021) - Alayed, Yasir; Loblaw, Andrew; McGuffin, Merrylee; Chung, Hans T.; Tseng, Chia-Lin; D'Alimonte, Laura; Cheung, Patrick; Liu, Stanley; Chu, William; Szumacher, Ewa; Helou, Joelle; Ravi, Ananth; et al.
Highlights: Single fraction high dose-rate brachytherapy has high local recurrence rate. Dose escalation with an MR-guided boost to the dominant lesion does not improve outcome. Single fraction protocols should not be used. Abstract: Purpose: Single-fraction HDR monotherapy for the treatment of localized prostate cancer is appealing, but published outcomes are discouraging. An approach to improve local control is MRI-guided focal dose-escalation to the dominant intraprostatic lesion (DIL). Here we report a comparison of outcomes from two phase II clinical trials with and without a focal boost. Methods: Patients had low or intermediate-risk disease. Patients in Trial1 received a single 19 Gy HDR implant to the whole prostate. Trial2 incorporated an additional MRI-guided focal DIL boost to at least 23 Gy. ADT was not allowed. Toxicities (CTCAEv4.0) and quality of life (EPIC) were collected. Biochemical failure (BF) was defined as nadir +2. Univariate and multivariate logistic regression analysis was conducted to search for predictors of BF. Results: Trial1 had 87 patients with a median follow-up of 62 months, while Trial2 had 60 patients with a median follow-up of 50 months. The five-year cumulative BF rate was 32.6% and 31.3%, respectively ( p = 0.9). 77.5% of failures were biopsy-confirmed local failures, all of which underwent local salvage therapy. The addition of a DIL boost was not associated with worse toxicity or QOL. Baseline PSA and Gleason score correlated with BF, but none of the dosimetric parameters was a significant predictor of BF. Conclusions: MRI-guided focal boost was safe and well tolerated, but did not improve local control after 19 Gy single-fraction HDR monotherapy, and the control rates were unacceptable. Single-fraction HDR monotherapy for prostate cancer should not be offered outside of clinical trials.